2006
DOI: 10.1002/uog.2818
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of 4D sonography with B‐flow imaging and spatio‐temporal image correlation (STIC) in the assessment of the anatomy of pulmonary arteries in fetuses with pulmonary atresia and ventricular septal defect

Abstract: Objectives To assess the reliability of two-dimensional gray-scale (2D) and color

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 28 publications
(36 reference statements)
4
50
0
Order By: Relevance
“…Our overall diagnostic accuracy was 81%, which is inside the range of 77-96% previously reported [1,2,3,4,18,19], although the GA at diagnosis was lower in our series. The accuracy in the CAT group was 80%, with the most common form corresponding to subtype 1 (fig.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our overall diagnostic accuracy was 81%, which is inside the range of 77-96% previously reported [1,2,3,4,18,19], although the GA at diagnosis was lower in our series. The accuracy in the CAT group was 80%, with the most common form corresponding to subtype 1 (fig.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have suggested that both sequential echocardiography [3,18] and 4D-STIC echocardiography [19,28] can be used to improve the differential diagnosis. In our series, 80% of the parents decided not to continue with the pregnancy, but we retrospectively analyzed 5 of the 6 misdiagnosed cases by 4D-STIC echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few reports on B-flow imaging of the umbilical cord and fetal cardiac imaging. [4][5][6][7][8] However, for potential users of this technique, the question is whether the images alone add new information.9 …”
mentioning
confidence: 99%
“…For example, power Doppler reconstructions of 3D and 4D volume data sets have been used to visualize the spatial configuration of abnormal vasculature in the fetal liver, 1,2 other vascular territories, 1,3 and abnormal arterial connections to the fetal heart. 4,5 Recently, 3D and 4D rendering algorithms, including the minimum projection mode, 6 the inversion mode, [7][8][9] and B-flow, [10][11][12][13][14] have been used to visualize normal and abnormal vascular connections to the fetal heart. However, these rendering algorithms frequently require image optimization, increasing the time needed for offline volume analysis.…”
mentioning
confidence: 99%